Proteomic analysis and antibacterial resistance mechanisms of Salmonella Enteritidis submitted to the inhibitory effect of Origanum vulgare essential oil, thymol and carvacrol - Barbosa, Lidiane Nunes [UNESP]; Alves, Fernanda Cristina Bergamo [UNESP]; Andrade, Bruna Fernanda Murbach Teles [UNESP]; Albano, Mariana [UNESP]; Rall, Vera Lucia Mores [UNESP]; Fernandes, Ana Angélica Henrique [UNESP]; Buzalaf, Marilia Afonso Rabelo; Leite, Aline de Lima; de Pontes, Leticia Gomes [UNESP]; dos Santos, Lucilene Delazari [UNESP]; Fernandes Junior, Ary [UNESP] (Elsevier, 2020)
Biological properties of natural products are an important research target and essential oils (EO) from aromatic plants with antimicrobial properties are well documented. However, their uses are limited, and the mechanisms underlying their antibacterial activity are still not well known. Therefore, our objective was to evaluate the antibacterial activities of Origanum vulgare EO, thymol and carvacrol against Salmonella Enteritidis ATCC 13076 strain, particularly regarding the bacterial proteic profile, enzymatic activities and DNA synthesis. Bacterial expressed proteins were evaluated using an untreated assay control and treatments with sublethal concentrations of oregano EO, carvacrol and thymol. The same protein extracts were also assayed for oxidative stress and energy metabolism enzyme activities, as well as effect on DNA synthesis. Protein expression outcomes revealed by 2D-SDS-PAGE, from antimicrobial actions, showed a stress response with differential expressions of chaperones and cellular protein synthesis mediated by the bacterial signaling system. In addition, Salmonella used a similar mechanism in defense against oxidative stress, for its survival. Thus, the antibacterial inhibitory activity of EO was preferentially associated with the presence of thymol and there was interference in protein regulation as well as DNA synthesis affected by these compounds. Significance: Antimicrobial activity of essential oils (EO) is already known. In this way, the understanding of how this activity occurs is a fundamental part to provide the practical and rational use of these substances. In the current scenario, where the emergence of resistant bacteria or even multiresistant bacteria against conventional antimicrobials, the search for alternatives becomes essential, since the discovery of new inhibitory substances does not occur at the same speed. The anti-Salmonella action allied to the knowledge about the biological processes affected by O. vulgare EO contribute to these bioactive compounds being effectively used as agents in the safety and shelf life of food in a future product, packaging or process where the antibacterial activity is safe and best used.
Keywords: 2D-SDS-PAGE; Natural antimicrobials; Protein homeostasis; Stress response